Aplikasi Teknik Polymerase Chain Reaction (PCR) Terhadap Variasi Gejala Penyakit Citrus Vein Phloem Degeneration (CVPD) pada Beberapa Jenis Daun Tanaman Jeruk - GUSTI PUTU DINTYA PUTRA; WAYAN ADIARTAYASA; MADE SRITAMIN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT Application Polymerase Chain Reaction (PCR) Technique to Variation Symptoms Disease Citrus Vein Phloem Degeneration (CVPD) on Several Types of Citrus Leaves CVPD disease is one of the major diseases in citrus plant. CVPD disease spread from plant to plant by insect vectors Diaphorina citri, and from one region to another region infected by seed. CVPD disease causes symptoms, the leaves become chlorotic with veins remain green. This study aims to determine the PCR method can detect CVPD of citrus from mild to severe symptoms. CVPD symptoms observed on several types of citrus leaves (Siam, Selayar, Besakih, Tejakula, Sweet, Purut, Lime, Lemo, and pomelo) showed chlorosis symptoms from mild to severe. Then the plants were symptomatic will be identified molecular in the Biotechnology Lab. After electrophoresis on almost all samples showed DNA bands with size 1160 bp. Therefore 1160 bp was had bacteri Liberobakter, the plants reacted positive with Liberobakter asiaticum Keyword: CVPD, Liberobacter asiaticum, PCR